Effect of Green Manure, Sesbania bispinosa Wight Amendment on Incidence of Sucking Insect Pests, their Predators and Yield in Organic Cotton - Jam Ghulam Mustafa Sahito; Tajwar Sultana Syed; Ghulam Hussain Abro; Inayatullah Rajpar (Journal of Basic & Applied Sciences, 2016)
Cotton holds the key importance in the economy of Pakistan, but its yield is severely affected due to the infestation of many insect pests. Farmers mostly rely on chemicals to control pests but their adverse effects on human health and their interests are also considerable. Therefore, this study was conducted over two years to evaluate the influence of amendment of soil with green manure (GM) Dhancha, Sesbania bispinosaWight on the population of cotton sucking insect pests and their predators. Significant impact of GM was found in lowering the population of sucking pests of cotton i.e., Thrips tabaci(Lind), Bemisia tabaci (Gennadus), Amrasca bigutulla bigutulla (Ishida) and Tetranychus urticae (Koch) during both years. Population of predators i.e., Chrysoperla carnea, Geocoris punctipesand Orius sp. was also higher in dhancha treated plots in comparison to control. Application of neem oil was found effective in lowering the population of sucking insect pests during 2014; whereas, application of C. carnea cards showed significant impact after the mid cotton season during 2015. Overall growth and yield parameters were better in dhancha amended organic cotton treatment in comparison to control.